EVALUASI KINERJA PEMERINTAHAN GERBANG RAJA - Efri novianto (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2013)
Vision development of Gerbang Raja in 2011–2015 is “A Society of Kutai Kartanegara that propesous and equitable”. Properous here interperetd as insufficient needs outward and inward. While justice interpreted the absence of discrimination and lack of rights, ability and opportunity for the community to be involved in various development fields (RPJMD. Kab. Kukar 2011-2015). This study use qualitative approach with two methods : descriftive and survey. based on the results of the study it can be concluded that :General government performance of Kutai kartanegara regency in fiscal year 2011 realization based activities can be categorized as either, considering the uptake average achieved to 70,18%. while in the first half of the fiscal year 2012 budget realization activities generally considered bad, because the average absorption in the first half only 12,05%. government performance of Kutai kartanegara Regency seen from the Gerbang Raja mission achievements summarized in RPJMD, considered quite successful because of the 44 performance indicators that were analyzed, 22 missions surpassed the set target. Government Performance Kutai Kartanegara seen from the level of public satisfaction with public services, majority of respondents perceive satisfied (56,9%) with the public services provided by government of Kutai Kartanegara. of it can be concluded that the public service has been executed well, judging from the level of people's satisfaction on the performance of public services in Kutai Kartanegara.Key words: vision, performance, community satisfaction